A new paradigm to explain the development of instability rutting in asphalt pavements. Issue 7 (2nd October 2020) - Simms, Reebie; Hernando, David; Roque, Reynaldo
Abstract : Using the most sophisticated models, rutting in asphalt pavements is currently explained as the result of the accumulation of vertical compressive strain due to air void reduction (i.e. densification) and lateral dilation of the asphalt mixture induced by repeated traffic loads, mainly during warmer seasons. However, instability rutting of asphalt mixture may not be fully explained by volume change alone. The primary objective of this study was to identify a potential mechanism of instability rutting consistent with transverse profiles observed in asphalt pavement. A finite element model of a radial truck tyre on a flexible pavement structure showed the existence of potential slip planes defined by a series of contiguous points along which the direction of maximum shear stress was aligned. Stress states along potential slip planes coupled high shear with low confinement, or even tension. The criticality of these stress states was studied by comparing shear stress to shear strength. It was found that stress states induced by a radial tyre, in addition to the reduction in asphalt mixture shear strength caused by repeated traffic loads and higher temperatures, may promote the development of a global shear plane under the tyre edge along which slip occurs. Rotation of a slipped zone, rather than volume change alone, may explain the development of ruts and lateral humps along the wheel path in agreement with transverse profiles observed in asphalt pavement.